Controversies in the management of deep neck space infection in children: an evidence‐based review. (30th June 2016) - Lawrence, R.; Bateman, N.
Abstract : Background: Deep neck space infection (DNSI) is defined as infection in the potential spaces and fascial planes of the neck. Early recognition of DNSI can be challenging due to the complex head and neck anatomy; hence, a high index of suspicion is required to prevent a delay in diagnosis and appropriate management. Objective of review: There remains a lack of consensus on the management of paediatric DNSI with many advocating a more aggressive approach with immediate surgical drainage, while others favour a more conservative approach with medical management in the first instance. The current literature on the management of paediatric DNSI is reviewed. Type of review and search strategy: A literature review performed in November 2015 searched PubMed using the terms 'deep neck space', 'infection', 'paediatric', 'pediatric', 'children', 'imaging', 'conservative', 'antibiotic' and 'surgery'. Articles not in the English language were excluded. Results: (i) Clinical presentation: Management of a compromised airway is the priority. Clinical history and examination enables the identification of the primary source of infection and presence of complications. (ii) Investigations: Laboratory and microbiological investigations should be appropriately targeted, and CT imaging is the modality utilised in most cases. The presence of specific complications may warrant other imaging modalities. (iii) Antibiotics: An evidence‐based antibiotic regime is proposed. (iv) Conservative treatment: In children lacking indications for surgical intervention, a trial 48 h of intravenous antibiotics (IV Abx) should be commenced. v) Surgical intervention: Indications include signs of airway compromise, presence of complications, no clinical improvement after 48 h of IV Abx, abscess >2.2 cm on CT imaging, age <4 years and ITU admission. Conclusions: An appreciation of head and neck anatomy is vital to understanding disease pathology and potential complications of DNSI, which may be life threatening. Both conservative and surgical approaches are viable treatment options and may compliment each other. Current evidence suggests that clinical management should be targeted towards the individual patient as factors such as age of the child may influence the balance of a conservative versus a surgical approach.